Endogenous circadian rhythms in pigment composition induce changes in photochemical efficiency in plant canopies. (30th March 2017) - García‐Plazaola, José Ignacio; Fernández‐Marín, Beatriz; Ferrio, Juan Pedro; Alday, Josu G.; Hoch, Günter; Landais, Damien; Milcu, Alexandru; Tissue, David T.; Voltas, Jordi; Gessler, Arthur; Roy, Jacques; Resco de Dios, Víctor
Abstract: There is increasing evidence that the circadian clock is a significant driver of photosynthesis that becomes apparent when environmental cues are experimentally held constant. We studied whether the composition of photosynthetic pigments is under circadian regulation, and whether pigment oscillations lead to rhythmic changes in photochemical efficiency. To address these questions, we maintained canopies of bean and cotton, after an entrainment phase, under constant (light or darkness) conditions for 30–48 h. Photosynthesis and quantum yield peaked at subjective noon, and non‐photochemical quenching peaked at night. These oscillations were not associated with parallel changes in carbohydrate content or xanthophyll cycle activity. We observed robust oscillations of Chl a / b during constant light in both species, and also under constant darkness in bean, peaking when it would have been night during the entrainment (subjective nights). These oscillations could be attributed to the synthesis and/or degradation of trimeric light‐harvesting complex II (reflected by the rhythmic changes in Chl a / b ), with the antenna size minimal at night and maximal around subjective noon. Considering together the oscillations of pigments and photochemistry, the observed pattern of changes is counterintuitive if we assume that the plant strategy is to avoid photodamage, but consistent with a strategy where non‐stressed plants maximize photosynthesis. Abstract : From chloroplasts to ecosystems, the circadian clock is a significant driver of photosynthesis, which becomes apparent when environmental cues are experimentally held constant over a few days. In the present study, we have investigated whether the composition of photosynthetic pigments is under circadian regulation. We show that carbon assimilation, stomatal conductance and quantum yield oscillated with a frequency close to 24 h, peaking around subjective noon. These changes were paralleled by robust oscillations of chlorophyll a / b both under constant light or darkness, indicating a rhythmic pattern of antenna‐size adjustment (minimal at night and maximal around noon). These results have important implications for future studies on pigment dynamics, particularly when using remote‐sensing platforms.